现代汉语介词“给”与印尼语 “untuk、kepada、oleh” 的比较 - Paula Aretha (Sinolingua: Journal of Chinese Studies, 2024)
The preposition word "给" is a hypothetical word widely used in modern Chinese. In Chinese grammar, the preposition word "给" has many meanings and the functions of using this word vary. Preposition words Indonesian, such as "for", "to", and "by" are similar to the preposition word "给" in modern Chinese. In this paper, we will analyze the Chinese preposition word "给" and the Indonesian preposition word "for", "to", and "by" to find out each of the functions of the word, so that we can also know the similarities and differences between them. And this can cause, Indonesian students who are learning Mandarin are confused and use it incorrectly. Indonesian students have been using their mother tongue since childhood before they learned Mandarin as their second language, so their mother tongue will definitely have an impact on learning Mandarin as the target language.  For example, the order of words in sentences between the two is different, so Indonesian students in the process of learning the preposition word "给", they use it incorrectly. Therefore, for Chinese teachers, we should think about the following points in our teaching: First, as qualified Chinese teachers, we must first understand the difference between Chinese grammar system and Indonesian, so as to remind students to avoid bias at any time in teaching. Secondly, as a teacher, you must be clear about the difficulties and key points in teaching, and repeatedly explain these two points to strengthen students' impressions of these key points and the difficulties to avoid bias in the future. Of course, we must also choose comprehensive textbooks, and for the shortcomings in textbooks, teachers must try their best to make up for these shortcomings.